School that protects: An action integrating the school into the protection network - Lina Rodrigues de Jesus, Maria; dos Santos, Valber Ricardo; Brito Almeida, Layon; de Souza Silva, Kesya (Guará Journal, 2025)
The "School That Protects" project is a partnership between the Ministry of Education and the Federal University of Espírito Santo’s Extension University. The project aims to provide resources for education professionals and the protection network to work on preventing and addressing various forms of violence against children and adolescents. This article presents the work of the project’s partners in the cities where it operates through university extension services, as well as some reflections on human rights education and the project’s perspectives.